Physiological Status Drives Metabolic Rate in Mediterranean Geckos Infected with Pentastomes. - Isabel C Caballero; Andrew J Sakla; Jillian T Detwiler; Marion Le Gall; Spencer T Behmer; Charles D Criscione (PLoS ONE)
Negative effects of parasites on their hosts are well documented, but the proximate mechanisms by which parasites reduce their host's fitness are poorly understood. For example, it has been suggested that parasites might be energetically demanding. However, a recent meta-analysis suggests that they have statistically insignificant effects on host resting metabolic rate (RMR). It is possible, though, that energetic costs associated with parasites are only manifested during and/or following periods of activity. Here, we measured CO2 production (a surrogate for metabolism) in Mediterranean geckos (Hemidactylus turcicus) infected with a lung parasite, the pentastome Raillietiella indica, under two physiological conditions: rested and recently active. In rested geckos, there was a negative, but non-significant association between the number of pentastomes (i.e., infection intensity) and CO2 production. In recently active geckos (chased for 3 minutes), we recorded CO2 production from its maximum value until it declined to a stationary phase. We analyzed this decline as a 3 phase function (initial decline, secondary decline, stationary). Geckos that were recently active showed, in the secondary phase, a significant decrease in CO2 production as pentastome intensity increased. Moreover, duration of the secondary phase showed a significant positive association with the number of pentastomes. These results suggest that the intensity of pentastome load exerts a weak effect on the metabolism of resting geckos, but a strong physiological effect on geckos that have recently been active; we speculate this occurs via mechanical constraints on breathing. Our results provide a potential mechanism by which pentastomes can reduce gecko fitness.